O DEBATE PREVIDENCIÁRIO CONTEMPORÂNEO: “perspectiva conservadora” versus “perspectiva das demandas por seguridade social” - Jessé Sales Rêgo (Universidade Federal do Maranhão, 2018)
The article discusses the ideological roots of the debate about the organization and management of social security systems in contemporary capitalist society. In this sense, two perspectives stand out, the “conservative perspective” and the “perspective of demands for social security”. It also discusses how this debate inﬂuences the current project of Reform of the Brazilian Social Security System.